2009
DOI: 10.5012/bkcs.2009.30.11.2595
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Hydrogen Bonding and Vibrational Analysis of N,N-Dimethylformamide Hexamer Cluster

Abstract: Hexamer cluster of N,N-dimethylformamide(DMF) based on the crystal structure was investigated for the equilibrium structure, the stabilization energies, and the vibrational properties in the density functional force field. The geometry (point group Ci) of fully optimized hexamer clustered DMF shows quite close similarity to the crystal structure weakly intermolecular hydrogen bonded each other. Stretching force constants for intermolecular hydrogen bonded methyl and formyl hydrogen atoms with nearby oxygen ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…In DMF, the first solvation shell shows the expected preference for antiparallel dipole orientation between molecules, while in DMAc, parallel dipoles maximize dispersion forces between the π-delocalized OC–N backbones and methyl groups . These results are consistent with Raman and IR spectroscopy and molecular dynamics studies of liquid DMF, all of which reported a highly structured first solvation shell with weak hydrogen bonding from carbonyl and methyl H atoms, in line with the “relatively short” C–H···OC contacts seen earlier by gas-phase electron diffraction. …”
Section: Introductionsupporting
confidence: 83%
“…In DMF, the first solvation shell shows the expected preference for antiparallel dipole orientation between molecules, while in DMAc, parallel dipoles maximize dispersion forces between the π-delocalized OC–N backbones and methyl groups . These results are consistent with Raman and IR spectroscopy and molecular dynamics studies of liquid DMF, all of which reported a highly structured first solvation shell with weak hydrogen bonding from carbonyl and methyl H atoms, in line with the “relatively short” C–H···OC contacts seen earlier by gas-phase electron diffraction. …”
Section: Introductionsupporting
confidence: 83%
“…However, strong vibrational features arising from adsorbed PVP or DMF were observed for all Ag colloids, demonstrating the strong surface-enhanced Raman scattering (SERS) effect of Ag surfaces. Their assignments (Table ) were made on the basis of previous Raman spectra of pure PVP and DMF, PVP and DMF in complexes, and PVP and DMF on metal colloids. , Ag–DMF particles exhibit the Ag–N and/or Ag–O Raman shift features at 222 cm –1 , while Ag–PVP cubes and Ag–PVP + DMF plates exhibit the same Ag–N and/or Ag–O vibrational features at 245 cm –1 . These results indicate that the interactions between the Ag surface and adsorbed capping ligands are similar for Ag–PVP cubes and Ag–PVP + DMF plates, in agreement with the above Ag 3d XPS results that Ag–PVP cubes and Ag–PVP + DMF plates exhibit similar Ag 3d binding energies.…”
Section: Results and Discussionmentioning
confidence: 99%